Sleep pattern in relation to recurrent osteoporotic fracture in the elderly - Li, Likang; Zeng, Haobin; Zhang, Bo; Xu, Xu; Chen, Maoshui; Li, Guowei (Frontiers in Public Health, 2022)
Background: Previous studies assessed the relationship between individual sleep behavior and fracture risk, rather than taking into account the joint complexity of the sleep behaviors. We aimed to explore the association between sleep pattern and risk of imminent recurrent osteoporotic fracture in older hospitalized patients due to an index osteoporotic fracture, where sleep pattern was evaluated as a combination incorporating five common sleep behaviors (insomnia, snoring, nocturnal sleep duration, daytime napping, and midnight waking up). Methods: We used data from a prospective cohort study for analyses. Patients who aged no less than 55 years and were admitted to hospital due to an index osteoporotic fracture were recruited. Sleep pattern was grouped as healthy, intermediate and poor pattern, based on the categorization of overall sleep scores. We used Cox proportional hazards models to explore sleep pattern in relation to imminent recurrent fracture. Results: We included a total of 185 elderly hospitalized patients for analyses: mean (± standard deviation) age = 71.5 ± 10.3 years; 87.0% females. During a mean follow-up of 14.7 months, there were 10 (5.4%) recurrent osteoporotic fractures observed. A significantly higher overall sleep score was found in patients with recurrent fracture when compared with those without fracture (3.20 vs. 2.36, p = 0.038). Both intermediate (p = 0.76) and poor sleep patterns (p = 0.093) were non-significantly associated with elevated risk of fracture when compared with healthy pattern. Per-one-increase in the overall sleep score was significantly related to increased risk of fracture: hazard ratio = 1.60 (95% confidence interval: 1.00 - 2.55) from multivariable model. Conclusions: Per-one-increase in the overall sleep score was found to significantly associate with 60% higher risk of imminent recurrent osteoporotic fracture in the elderly; and intermediate and poor sleep patterns were non-significantly related with increased risk of recurrent fracture. More high-quality evidence is required to further evaluate the relationship between sleep pattern and risk of recurrent osteoporotic fracture in the elderly.